Effects of Youth Empowerment Strategies on Conflict Resolutions in the Niger-Delta of Nigeria: Evidence from Cross River State - Ofem, NI; Ajayi, AR (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> The Niger Delta region of Nigeria has been ridden by youth restiveness and yet several intervention program have not yielded positive results. The study, therefore, evaluates the impact of youth empowerment strategies on conflict resolution using an ordered probit regression model. The study reveals that youth educational programs, provision of infrastructures and credit facilities showed significant effects as tools for conflict resolution. Employment opportunities and income indicated positive results yet they were not significant. This indicates that youth empowerment strategies must be sustainable if they have to make reasonable impact on conflict management. DOI: http://dx.doi.org/10.3329/jard.v6i1.1671 J Agric Rural Dev 6(1&2), 139-146, June 2008